Identification and characterization of long noncoding RNAs involved in the aluminum stress response in Medicago truncatula via genome-wide analysis - Gui, Qihui; Yang, Zhengyu; Chen, Chao; Yang, Feng; Wang, Song; Dong, Rui (Frontiers in Plant Science, 2022)
Numerous studies have shown that plant long noncoding RNAs (lncRNAs) play an important regulatory role in the plant response to environmental stress. However, there are no reports on lncRNAs regulating and enhancing aluminum (Al) stress tolerance in legumes. This study analyzed the role of lncRNAs in response to Al stress in the legume model plant Medicago truncatula. A total of 219.49 Gb clean data were generated: 3,284 lncRNA genes were identified, of which 515 were differentially expressed, and 1,254 new genes were functionally annotated through database alignment. We further predicted and classified putative targets of these lncRNAs and found that they were enriched in biological processes and metabolic pathways such as plant hormone signal transduction, cell wall modification and the tricarboxylic acid (TCA) cycle. Finally, we characterized the functions of 2 Al-activated-malate-transporter-related lncRNAs in yeast. The recombinant plasmids of MSTRG.12506.5 and MSTRG.34338.20 were transformed into yeast, and these yeast exhibited better growth than those carrying empty vectors on medium supplemented with 10 μM AlCl3 and showed that they have biological functions affording Al stress tolerance. These findings suggest that lncRNAs are involved in regulating plant responses to Al stress. Our findings help to understand the role of lncRNAs in the response to Al stress in legumes and provide candidate lncRNAs for further studies.